Higher-pitched bird song towards the coast supports a role for selection in ocean noise avoidance. Issue 1 (2nd January 2022) - Sebastianelli, Matteo; Blumstein, Daniel T.; Kirschel, Alexander N. G.
ABSTRACT: Effective communication in birds is often hampered by background noise, with much research focusing on the effect of anthropogenic noise on passerine bird song. Continuous low-pitch natural noise can drive changes in both spectral and temporal patterning of bird vocalisations, but the extent to which these effects may also affect birds that lack vocal learning is not well understood. We used a gradient of exposure to natural low-frequency noise to assess whether it exerts selective pressure on innate vocalisations. We tested whether three species of Pogoniulus tinkerbirds adapt their song when exposed to continuous low-frequency noise from ocean surf. We show that dominant frequency increases the closer birds are to the coast in at least two species, indicating that ocean surf sound may apply a selective pressure on songs. Tinkerbirds adapt their songs by increasing dominant frequency to avoid masking by ambient noise, therefore improving long-range communication. Our study provides evidence that natural ambient noise affects vocalisations in birds whose songs develop innately. We believe that our results can also be extrapolated in the context of anthropogenic noise pollution, hence providing a baseline for the study of the effects of low-frequency ambient noise on birds that lack vocal learning.